Task-based navigation of a taxonomy interface to a digital repository - Khoo, Christopher S. G. (2014)
Introduction. This is a study of hierarchical navigation; how users browse a taxonomy-based interface to an organizational repository to locate information resources. The study is part of a project to develop a taxonomy for an library and information science department to organize resources and support user browsing in a digital repository. Method. The data collection was carried out using task-based navigation exercises with twenty-two participants. A cognitive framework of hierarchical navigation is proposed, involving the cognitive process of matching context, topic and/or resource type concepts to taxonomy categories. Analysis. The analysis was mainly qualitative, supplemented with simple statistics and measures of prevision and recall, and error analysis. Results. Though users often use the topic concept in making navigation choices, they sometimes make use of context and resource-type concepts. Users infer a variety of relationships between a task concept and a taxonomy category, including the application area, associated tool, associated process/procedure/technique, associated institution and academic discipline. Conclusions. Users prefer to use common or generic associations in selecting categories to browse, rather than formal disciplinary relations. Some users prefer to search by people groups, contexts and institutions, rather than by subject categories. Users have difficulty distinguishing between various kinds of document and resource types.